High Efficient and Stable Solid Solar Cell: Based on FeS2 Nanocrystals and P3HT: PCBM. (August 2015) - Luo, Lingli; Luan, Weiling; Yuan, Binxia; Zhang, Chengxi; Jin, Lin
Abstract: Nanocrystals(NCs)/polymer solid solar cells have the advantages of low-cost, simple process and flexible manufacturing. FeS2 NCs is a kind of semiconductor with optical absorption in visible and near-infrared area, match well with the solar radiation spectrum. The solid solar cells based on FeS2 NCs, poly(3-hexylthiophene) (P3HT) and phenyl-C61 -butyric acid methyl ester(PCBM), were prepared and achieved a photovoltaic conversion efficiency( PCE ) of 3.0%. Besides, the device showed high stability with 83.3% of its initial efficiency remained after 15 weeks of exposure in air and stable performance in the range of 20-80 o C. The PCE fluctuation magnitudes were also found smaller than quantum-dot sensitized solar cell (QDSSC) under the same condition.